Histosols of South Florida: Past, Present, and Future - Xue Bai; Yuncong Li; Noel Manirakiza; Christine Coffin; Jehangir H. Bhadha (EDIS)
This factsheet presents a comprehensive overview of Histosols, also known as organic soils, in South Florida, focusing on their distribution, formation, properties, and significance. Histosols cover significant areas in Florida, especially within the Everglades Agricultural Area (EAA), and are pivotal in supporting the region's sugarcane production. Their formation is influenced by organic parent materials, the tropical climate, vegetation types, topography, and time, which together shape their unique chemical, physical, and biological properties. Moreover, this publication reviews past developments and anticipates future changes in Histosol classification and management. By revealing the past, present, and future of Histosols in South Florida, this publication can help improve land management in the region and enhance the understanding of Histosols for audiences including agricultural producers, Extension agents, state and local agencies, decision-makers, researchers, and students.